Deskripsi Kemampuan Pemahaman Konsep Matematika Siswa pada Materi Sistem Persamaan Linear Tiga Variabel - Nur Baina; Tedy Machmud; Abdul Wahab Abdullah (Jambura Journal of Mathematics Education, 2022)
This article discusses describing the ability to understand a student's mathematical concepts in the material of a three-variable system of linear equations. The strategy used is descriptive qualitative. The data sources of this research are the results of tests and interviews. The research subjects from a total of 35 students of class X MAS AL-Falah Limboto Barat who were selected based on the results of student’s understanding of mathematical concepts on the material of a three-variable system of linear equations, namely in each category one student was selected to represent each category. The data collection technique was carried out by means of an essay test as a supporting instrument and an interview as the main instrument. Essay test to obtain data on student’s ability to understand mathematical concepts in terms of 3 indicators, namely; (1) restate a concept, (2) provide examples instead of examples, (3) apply concepts or algorithms in problem-solving. The results of the study show that the ability to understand student’s mathematical concepts is still classified in the low category